2013
DOI: 10.1039/c3cc40568k
|View full text |Cite
|
Sign up to set email alerts
|

High-rate lithium storage of anatase TiO2 crystals doped with both nitrogen and sulfur

Abstract: Anatase TiO2 nanocrystals doped with nitrogen and sulfur, where substitutional N and S atoms for lattice O, respectively, locate in the bulk and the surface layer of the crystals, were designed and prepared. As a result of remarkably lowered electronic resistance, the N/S doped TiO2 shows a superior high rate lithium storage capability to that of reference TiO2 nanocrystals, though the former has a larger particle size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…The width of this semi-circle gives the approximate overall charge transfer resistance (R ct ). 28 It was found that the Li 4 Cyclic voltammograms (CV) of the two batteries was conducted to study the function of carbon for suppressing gassing, as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…The width of this semi-circle gives the approximate overall charge transfer resistance (R ct ). 28 It was found that the Li 4 Cyclic voltammograms (CV) of the two batteries was conducted to study the function of carbon for suppressing gassing, as shown in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] However, the poor conductivity of TiO 2 results in great capacity fading and a poor rate capability, which is unfavorable for its large-scale application. According to reported in the literature, [14][15][16][17] tuning of the conductivity of TiO 2 by doping is a positive route to enhance its conductivity and subsequent excellent electrochemical performance. For instance, Zheng et al reported C À N codoped mesoporous TiO 2 , which exhibited a high capacity of about 272 mA h g À1 at a current density of 0.1 C, with a surface area of 44.29 m 2 g À1 through the hydrolysis of Abstract: Compositing amorphous TiO 2 with nitrogen-doped carbon through TiÀN bonding to form an amorphous TiO 2 /N-doped carbon hybrid (denoted a-TiO 2 /C À N) has been achieved by a two-step hydrothermalcalcining method with hydrazine hydrate as an inhibitor and nitrogen source.…”
Section: Introductionmentioning
confidence: 93%
“…First, the porous structure could effectively shorten the diffusion pathway of lithium ions and electrons, increase the high contact area between electrolyte and electrode, and provide good accommodation of strain during cycling. [14][15][16][17][18] Second, compositing materials with carbon can improve the electrochemical conductivity and release the volume expansion efficiently, and subsequently, improve the cycling stability. [1,2] In particular, nitrogen doping can generate more defects in the materials and provide more active sites for lithium-ion storage sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. 30 Accordingly, the interstitial/substituted-N co-doped TiO 2 -B (hereafter denoted as I/S-TiO 2 ) is expected to possess a higher electronic conductivity than those of the interstitial-N doped TiO 2 -B (hereafter denoted as I-TiO 2 ) and pure TiO 2 -B (hereafter denoted as P-TiO 2 ). As shown in Table 1, dc conductivity measurement shows that the electronic conductivity of the pure TiO 2 -B nanowires is 3.01 × 10 −11 S cm …”
Section: Morphology and Microstructure Characterizationmentioning
confidence: 99%